Chia seed oil-candelilla wax oleogels structural features and viscoelasticity are enhanced by annealing. (January 2022) - Trujillo-Ramírez, D.; Reyes, I.; Lobato-Calleros, C.; Vernon-Carter, E.J.; Alvarez-Ramirez, J.
Abstract: Chia seed oil-candelilla wax (3 g/100 g) oleogel was prepared and subjected to annealing at three different temperatures (30, 35 and 40 °C). Light microscopy images showed the presence of needle-like crystals structures dispersed in the oil phase. Annealing disrupted the crystalline structures by reducing their number. Wide-angle X-ray dispersion analysis showed that the annealed oleogels did not inherit the pristine candelilla wax crystallinity. Small-angle X-ray dispersion analysis showed that the needle-like structures were transformed into platelets after annealing. The storage G′ and loss G″ moduli values were boosted after annealing, indicating that the annealing process induced a strong reorganization of the oleogel structure. FTIR analysis indicated that unsaturated ester groups from candelilla wax and chia seed oil can act as surfactants that, in combination with platelet structures from n-alkanes, reconfigure the structure of oleogels during the annealing process. Overall, the results showed that annealing is a suitable process for oleogel strengthening when wax contents are relatively low. Highlights: Chia seed oil (ChSO)-candelilla wax (CW, 3% w/w) oleogels were made and annealed Annealing temperature (30, 35, 40 °C) boosted the viscoelasticity of the oleogels Upon annealing, reconfiguration of the oleogels structure takes place FTIR indicates that ChSO and CW ester groups may interact with CW platelet structures This simple process allows to form strong ChSO oleogels with low contents of CW